Design and development of noise detector at hangar aircraft training organisation / Norsiah Sukardy - Norsiah , Sukardy (2018)
Hearing problem is one of the most common disabilities among personnel at hangar. They are exposure to high noise from the aircraft engine, ground power unit (gpu), auxiliary power unit (apu), machinery, towing vehicles and rivet machine. Many of the posts have high noise levels, and particular ratings have high exposure. These are especially for the peak level of sound emission. If results of higher risk can be identified, then prevention precaution can be focused. Duty as technician, skill students, instructors, engineers and pilot ratings are at high risk for hearing loss, this study looked at medical hearing test records for nearly 100,000 enlisted AM personnel over the period of 2004 to 2017. Investigation on these matter have been done by doing analysis and study through survey and questionnaires . Collection of questionnaires from five (5) major hangar in Selangor are used to investigate the underlying hearing impairment. The design and development of Prototype Noise Detector has been created to assess the effect of this invention to reduce early hearing problems. Excessive hearing senses may persist and other problems due to noise can be overcome.